A simulation of the applied bias effect of tunnelling probability in quadruple barrier Si/SiO2 system - Purwiyanti, S.; Nuryadi, R.; Hartanto, D. (Proceedings of the 2011 International Conference on Electrical Engineering and Informatics, 2011)
Recently, multiple quantum wells structure are often used in the laser and diode applications in order to increase their efficiency. In this structure, electron tunnelling phenomena from a quantum well to another well play a key role in electronic transport itself. Tunnelling is a quantum mechanical phenomenon where an electron is commonly represented by its wavefunction. This paper presents a numerical simulation of electron tunnelling probability on three quantum wells (quadruple barrier) Si/SiO 2 system focusing the applied bias effect on the tunnelling probability. The tunneling probability is calculated by solving the Schrodinger's equations through potential barrier using transfer matrix method. The simulation results show the mini-band formation due to the appearance of discrete energy group. We also found that the applied bias on this structure causes the changes in tunnelling probability and discrete energy gap. Therefore, the control of voltage bias and device structure is required in order to obtain expected characteristic of multiple quantum well structure.